Unraveling Policy Overlaps in Indonesia’s National Development Planning System - Muhammad Arsad; Irwan Noor; Firda Hidayati (The Journal of Indonesia Sustainable Development Planning, 2025)
Indonesia's development governance faces persistent structural challenges: policy overlaps that undermine coherence in planning, performance management, and budgeting. This commentary adopts a systems level perspective to examine how fragmented mandates and institutional silos collectively shape governance complexity, directly affecting development outcomes at the subnational level while drawing lessons from international reform experiences. Indonesia's development planning architecture consists of the National Development Planning System (SPPN), the Government Performance Accountability System (SAKIP), and performance-based budgeting mechanisms. While established to enhance governance quality, public administration scholarship demonstrates that proliferating policy tools and institutional actors increase policy incoherence and institutional fragmentation (Peters, 2015). Indonesia's planning and performance systems evolve within separate institutional logics, creating what Moynihan (2008) conceptualizes as decoupled performance systems where planning, performance measurement, and budgeting remain insufficiently integrated. This fragmentation is reinforced by goal ambiguity (Rainey, 2009), as SPPN prioritizes development targets while SAKIP emphasizes organizational accountability. Fragmented approaches among key government bodies weaken interministerial coordination and exacerbate policy inconsistencies (O'Leary & Bingham, 2009). with this silo mentality being particularly evident in the Ministry of Home Affairs, the Ministry for Administrative and Bureaucratic Reform, and the Ministry of Finance.